Perbandingan Konsep Politik Dakwah Sayyid Qutb dan Hassan Hanafi - Firman Hidayat; Malki Ahmad Nasir (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This study discusses and analyzes the political concept of Da'wah by Sayyid Qutb and Hassan Hanafi as well as dialogues, both of whom are of the view that Islam is not a religion related to creed. However, Islam is a religion that perfectly regulates all life, including in building civilization, especially regarding the politics of Islamic da'wah. Sayyid Qutb with the thought of his commentary Fii Zhilaalil Qur'an, he said that the thoughts that support the politics of da'wah are divided into three parts. The first is the general rule (basic policy of da'wah politics), the second is the principles of the methodology of da'wah politics, and the third is the system of da'wah political movement (organization of the da'wah movement). As for Hassan Hanafi with his al-yasar al-Islami, he is try to study a lot about the Islamic revival, the Islamic revolution, and the unity of the Ummah with his very famous project, al-turath wa al-tajdid. West and the last attitude towards the reality and conditions of contemporary Muslims. The object of research by Sayyid Qutb and Hassan Hanafi is about the concept of da'wah politics using comparative methods and including library research, by conducting activities to find primary and secondary sources qualitatively. Abstrak. Penelitian ini membahas dan menganalisa konsep politik dakwah Sayyid Qutb dan Hassan Hanafi juga mendialogkannya, keduanya berpandangan bahwa Islam bukanlah agama yang berkaitan tentang akidah belaka. Akan tetapi, Islam merupakan agama yang mengatur semua kehidupan secara sempurna termasuk dalam membangun peradaban politik dakwah Islam. Sayyid Qutb dengan pemikiran kitab tafsirnya Fii Zhilaalil Qur`an, ia mengatakan bahwa pemikiran yang menunjang politik dakwah dibagi menjadi tiga bagian. Pertama Kaidah Umum (Kebijakan dasar politik dakwah), kedua Prinsp-prinsip metodologi politik dakwah, ketiga sistem gerakan politik dakwah (organisasi gerakan dakwah). Adapun Hassan Hanafi dengan ide kiri Islamnya, mencoba menelaah tentang kebangkitan Islam, revolusi Islam, dan kesatuan umat dengan garapan proyeknya yang sangat terkenal yaitu al-turath wa al-tajdid, ada tiga pilar untuk merealisasikannya yaitu: sikap terhadap masa lalu, sikap terhadap Barat dan yang terakhir sikap terhadap realitas dan kondisi muslim kontemporer. Objek penelitian pemikiran Sayyid Qutb dan Hassan Hanafi adalah mengenai konsep politik dakwah dengan menggunakan metode komparatif dan termasuk penelitian library research, dengan melakukan kegiatan mencari sumber primer dan sekunder secara kualitatif.